Korea : Background Papers. (IMF Staff Country Reports; Country Report, 1996)
This Background Paper provides a broad overview of the structure and characteristics of public finances in Korea, and discusses fiscal policy against the background of the medium-term objectives. The analysis shows that despite constraints imposed by the institutional framework, the government has managed to maintain tight budgetary control. The paper analyzes trends in the size and composition of central government expenditure, revenue, financing, and debt. It also evaluates the stance of fiscal policy on the basis of summary indicators.